State of food security & nutrition in Bangladesh 2011 - James P Grant School of Public Health (JPGSPH) and Helen Keller International (HKI) (BRAC University, 2014)
Food Security and Nutrition Surveillance Project Report; Lead Analyst and Writer: Jillian L. Waid Editor-in-chief: Alayne Adams Other Contributors: Feroz Ahmed, Hossain Khan, Erica Khetran, Shannon King, Asheq Rahman, and Rafae Wathra.